Longitudinal pathways of exclusive and polytobacco hookah use among youth, young adults and adults in the USA: findings from the PATH Study Waves 1–3 (2013–2016). (22nd April 2020) - Sharma, Eva; Bansal-Travers, Maansi; Edwards, Kathryn C; Halenar, Michael J; Taylor, Kristie A; Kasza, Karin A; Day, Hannah; Hammad, Hoda T; Anic, Gabriella; Limpert, Jean; Gardner, Lisa D; Borek, Nicolette; et al.
Abstract : Objective: The goal of this study is to examine cross-sectional rates of use and longitudinal pathways of hookah use among US youth (ages 12-17), young adults (ages 18-24), and adults 25+ (ages 25 and older). Design: Data were drawn from the first three waves (2013–2016) of the Population Assessment of Tobacco and Health Study, a nationally representative, longitudinal cohort study of US adults and youth. Respondents with data at all three waves (youth, n=11 046; young adults, n=6478; adults 25+, n=17 188) were included in longitudinal analyses. Results: Young adults had higher ever, past 12-month (P12M) and past 30-day cross-sectional prevalence of hookah use at each wave than youth or adults 25+. The majority of Wave 1 (W1) hookah users were P12M users of other tobacco products (youth: 73.9%, young adults: 80.5%, adults 25+: 83.2%). Most youth and adult W1 P12M hookah users discontinued use in Wave 2 or Wave 3 (youth: 58.0%, young adults: 47.5%, adults 25+: 63.4%). Most W1 P12M hookah polytobacco users used cigarettes (youth: 49.4%, young adults: 59.4%, adults 25+: 63.2%) and had lower rates of quitting all tobacco than exclusive hookah users or hookah polytobacco users who did not use cigarettes. Conclusions: Hookah use is more common among young adults than among youth or adults 25+. Discontinuing hookah use is the most common pathway among exclusive or polytobacco hookah users. Understanding longitudinal transitions in hookah use is important in understanding behavioural outcomes at the population level.